A humanist-metabolic configuration of the residential high-rise enriching urban living through selectability and customizability in urban dwelling typologies - Gamboa, Deodatu Augustus M. (College of Architecture, University of the Philippines Diliman, 2022)
The residential condominium typology is not only a typology of a building but a typology of urban living. However, residential condominiums as we know them are detrimental in two key aspects: their social impacts on the city (social exclusion, deepening spatial inequalities) and their myriad impacts on the individual, definitive to what is referred to as the condominium lifestyle. This project seeks to redefine the typology of urban living, by re-examining the typology of the urban dwelling: the ubiquitous, problematic, and currently increasing paradigm that is the high-rise residential. New living models, Alternative Construction Methods, Re-imagined Communities, and New Notions of Affordability are the main toolkits in designing this project. The ideals of Metabolist architecture (Kisho Kurokawa) and humanist architecture (WOHA Architects) are integrated in this design project. It is proposed that customizability and selectability in modular pre-fabrication (Kurokawa, 1982), safe and functions are keys toward reshaping urban dwelling to its next frontier, therefore redefining urban living-- one that nourishers the individual, the community, and the city -- in the midst of urban density.